2001
DOI: 10.1068/a33225
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Framework for Understanding and Analysing Attitudes towards Household-Waste Management

Abstract: The problem of household waste poses an international dilemma. The blueprint for worldwide sustainable development agreed by national leaders in Rio de Janeiro in 1992, Agenda 21 (UNCED, 1992), highlighted waste from domestic sources as a major barrier to achieving environmental sustainability in the 21st century. The householdwaste problem is global in its dimension, but has recently leapt onto the political agenda in developed nations as the stark reality emerges that there are fewer and fewer sites suitable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
168
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(179 citation statements)
references
References 39 publications
7
168
1
2
Order By: Relevance
“…There is a significant current in the literature 6 that has analyzed agents' environmental behavior in the context of the mixed public good, where the benefit deriving from the private component of the good leads to individual equilibrium choices that support environmental targets: these 'choices' often go beyond legal and contractual obligations. In addition, great interest has been devoted to including individual environmental behavior within psychological literature (Barr et al, 2001;De Young, 1996). In these works, the non-pecuniary levers of environmental behavior are attributed to different norms of behavior as altruism, social or moral norms, warm-glow and eco-centrism.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…There is a significant current in the literature 6 that has analyzed agents' environmental behavior in the context of the mixed public good, where the benefit deriving from the private component of the good leads to individual equilibrium choices that support environmental targets: these 'choices' often go beyond legal and contractual obligations. In addition, great interest has been devoted to including individual environmental behavior within psychological literature (Barr et al, 2001;De Young, 1996). In these works, the non-pecuniary levers of environmental behavior are attributed to different norms of behavior as altruism, social or moral norms, warm-glow and eco-centrism.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The studies which have included this variable unambiguously show a significant correlation between recycling behaviour and dwelling type, as represented in Fig. 5 [4,9,21,22,26,33,36]. Most of the findings on this issue make it possible to state that private housing (single-family dwelling) positively influences recycling behaviour.…”
Section: Socio-demographic Variablesmentioning
confidence: 93%
“…4). Some authors have found a relationship between recycling behaviour and age [10,[20][21][22][23][24][25][26][27][28][29], but others report no significant correlation [4,7,[30][31][32][33].…”
Section: Socio-demographic Variablesmentioning
confidence: 99%
See 2 more Smart Citations